Distinct metabolism of apolipoproteins (a) and B-100 within plasma lipoprotein(a) - Diffenderfer, Margaret R.; Lamon-Fava, Stefania; Marcovina, Santica M.; Barrett, P. Hugh R.; Lel, Julian; Dolnikowski, Gregory G.; Berglund, Lars; Schaefer, Ernst J. (Metabolism, clinical and experimental, 2016)
Lipoprotein(a) [Lp(a)] is mainly similar in composition to LDL, but differs in having apolipoprotein (apo) (a) covalently linked to apoB-100. Our purpose was to examine the individual metabolism of apo(a) and apoB-100 within plasma Lp(a). The kinetics of apo(a) and apoB-100 in plasma Lp(a) were assessed in four men with dyslipidemia [Lp(a) concentration: 8.9–124.7nmol/L]. All subjects received a primed constant infusion of [5,5,5-2H3] L-leucine while in the constantly fed state. Lp(a) was immunoprecipitated directly from whole plasma; apo(a) and apoB-100 were separated by gel electrophoresis; and isotopic enrichment was determined by gas chromatography/mass spectrometry. Multicompartmental modeling analysis indicated that the median fractional catabolic rates of apo(a) and apoB-100 within Lp(a) were significantly different at 0.104 and 0.263 pools/day, respectively (P=0.04). The median Lp(a) apo(a) production rate at 0.248nmol/kg·day−1 was significantly lower than that of Lp(a) apoB-100 at 0.514nmol/kg·day−1 (P=0.03). Our data indicate that apo(a) has a plasma residence time (11days) that is more than twice as long as that of apoB-100 (4days) within Lp(a), supporting the concept that apo(a) and apoB-100 within plasma Lp(a) are not catabolized from the bloodstream as a unit in humans in the fed state.